The Eurosystem operational framework, use of colleteral and liquidity distribution in the euro area: towards a single interbank market? - Vento, Gianfranco A. (PSL Quarterly Review, 2012)
This paper analyses the current operational framework chosen to implement single monetary policy in the euro area, pointing out the effects of certain technical choices in the field of monetary policy instruments on the interbank market and bank treasuries. In particular, I examine how the tender typology adopted for main refinancing operations affects overbidding and underbidding, as well as efficiency in bank liquidity management. I then go on to analyse the technical features of unsecured interbank markets in the euro area in order to determine whether a screen-based framework leads to more efficient liquidity management than achieved in over-the-counter markets. In accordance with the averaging provision mechanism, minimum reserves during the maintenance period in Italy, where the interbank market is electronic-based, are taken as indicators of efficiency in this market. On the evidence of the data, it seems that Italian banks can reduce the opportunity cost of maintaining minimum reserves, also performing intertemporal arbitrages between the interbank market and their reserve accounts. Finally, the focus comes on cross border differences in the use of collateral within the euro area in order to analyse the projects currently debated for the reform of collateral lists. JEL Codes: E43, E52